Détails d’ordres: On Forgotten Graphical Series by Jacques Androuet du Cerceau the Elder - Efimova, Elena A. (Actual Problems of Theory and History of Art, 2023)
The article is devoted to the study of a group of drawings and etchings by the French architect and engraver Jacques Androuet du Cerceau, known as Détails d’ordres. The attribution of these drawings to Du Сerceau has been recently questioned, but the author of the article provides arguments in favor of Du Cerceau’s authorship. The detailed analysis carried out by the author reveals similarities between the above-mentioned group not only with the Italian albums of the early 16th century, but also with a large group of sources from the 1530-1540s.The latter include: Destaileur A, B, and C albums from the State Hermitage Museum and their analogues from various collections, such as archaeological studies of the monuments of Verona by Giovanni Caroto, published in 1540 by T. Sarayna, engravings of Roman antiquities, made in 1530th by anonymous monogrammistes PS and GA, as well as the drawings of Roman monuments by Philibert Delorme, Andrea Palladio, and Sebastiano Serlio. The author concludes on the important role of this group of drawings and etchings in the formation of Du Cerceau’s architectural concept during his transition from a free and variant attitude toward the ancient architectural form to the strict norms of Serlio’s order theory.